PENGARUH GAYA HIDUP DAN PERSEPSI MAHASISWA TERHADAP KEPUTUSAN PEMBELIAN SECARA ONLINE DI KOTA PALEMBANG - SRI RAHAYU; ZUHRIYAH .; SILVIA BONITA (Program Studi Magister Manajemen FE Unsri, 2015)
Formulation of the problem was whether or not there is a significant the influence of lifestyle and student perceptions on purchasing decision by online in Palembang. The study aimed for finding out between lifestyle and student perceptions on purchasing decision by online in Palembang. The study was conducted by using associative for finding out whether or not lifestyle and student perceptions influence on purchasing decision by online Palembang. There were two variables; (1) lifestyle and student perceptions and (2) dependence variable was Purchasing decision that developed to be 14 indicators. The population was all of active students at private universities of Palembang. The sample was 346 by using purposive sampling. The data was primary data as source analysis. The data was collected by using questionnaire. The data was analyzed by using multiple linier regression. The result showed that there was a significant influence between lifestyle and student perceptions on purchasing decision by online in Palembang.